Individual speed control models for swimmers - Rodionov, V. A.; Rodionova, M. A.; Inake, E. K. (Theory and Practice of Physical Culture, 2019)
Training process control and management may be efficient enough only when the coach knows exactly what the effects of one or another training tool on the trainee`s body are. It is quite common to classify a training cycle into the workload intensity zones with the relevant heart rates and specific energy systems mobilization rates. Most of the national experts prefer the workload control by speed, with the individual best competitive speeds used as reference points for progress. Objective of the study was to consider theoretical grounds for and rate benefits of the individual speed control model for swimmers. Sampled for the study were the 16-17 year old sport excellence group trainees from Surgut State University, Neftyanik CYORSS and some other sport schools in Surgut (Khanty-Mansi Autonomous Yugra Area) qualified Candidate Masters of Sport and split up into Experimental (EG) and Reference (RG) Groups. The RG trainings were controlled by the traditional intensity zoning and HR test method; and the EG trainings were driven by the individual speed control models. Comparative analysis of the special physical fitness test rates of both groups showed the intensity zoning method being more sensitive and efficient for the training workload control purposes.